Harnessing Islamic Education for Agricultural Empowerment: The Islamic Boarding School Model in Indonesia - Nurlaili; Warnaen, Andi; Ugik, Romadi; Haryanto, Yoyon (Jurnal Penyuluhan Pertanian, 2025)
This research investigates the role of Islamic Boarding School in empowering Santri-farmers to achieve agricultural self-reliance in Indonesia, which addresses crucial issues of farmer regeneration and rural economic development. This research examines Islamic Boarding School-based agricultural empowerment programs and the level of empowerment of santri-farmers. The article focuses on a unique Islamic Boarding School model that integrates Islamic education with practical agrarian skills. Using a quantitative research design, this study collected data from Santri Farmers in three Islamic Boarding School in East Java, Indonesia, representing different institutions (Salafiyah, Modern, and Integrated).  The total population was 318 Santri Farmers, from which a sample of 116 participants was selected using a combination of simple random sampling and census techniques. Data were collected mainly through questionnaires and analyzed using descriptive statistics to measure the level of empowerment. The study revealed that Islamic Boarding School contributes to the agricultural empowerment of Santri-farmers. Effective empowerment activities include integrating agricultural education with religious education, providing agribusiness assistance, agricultural extension, and facilitating market access. Santri-farmers show a high level of empowerment, especially in terms of agricultural technical skills, resource management, and communication. Meanwhile, mastery of information technology is still lacking.